Histological method to study winter physiological dormancy in leaf buds of "San Castrese" and "Laycot" apricot, Prunus armeniaca L. - N. Valentini; A. Ponso; E. Ruffa; G. Me; B. Dore (Journal of Biological Research, 2009)
A new method of cryostabilization and embedding in a polar resin, performed at -20°C under controlled vacuum, was used to microscopically observe morphological and histochemical changes in leaf buds of apricot collected during the rest period. In order to determine the date of endodormancy breaking, ten twing of two varieties (San Castrese and Laycot) were collected weekly from November to February and held under controlled conditions. At the same time, ten leaf buds from each variety were collected. The stained sections obtained revealed good preservation of tissue and cell structures, which allowed the study of dormancy. Moreover the observation of lipids and waxes that in traditional inclusion methods were lost was allowed. The histological-cryostabilization method revealed changes of cell componets, such as different amounts of starch and lipid, size of cells, differences in colour and brightness of nuclei from buds which were completely dormant to metabolically active.